Reconstruction of Facial Skin and Soft Tissue Defects Based on the Unit Principles - Ogino, Akihiro; Onishi, Kiyoshi; Okada, Emi; Hayashi, Akiteru; Maruyama, Yu (Japanese Journal of Surgical Wound Care, 2012)
In the reconstruction of skin and soft tissue defects caused by tumor excision and trauma, it can be difficult to decide whether to use a suture closing or a local flap. Judgment should be based on the skin properties of the defect and the surrounding anatomical landmarks. We have applied the unit principles for facial reconstruction with satisfactory results. These principles are also extremely beneficial for obtaining natural contour and symmetry in the face. It is important not only to understand the configuration of the unit for reconstruction, but also to select the most suitable donor site and reconstructive procedure, since these also affect the aesthetic results.